Poly Acryl Amide as Acid Corrosion Inhibitor of C-steel in 15% HCl - Yaqoob, Ghassan Burhan (Journal of Petroleum Research and Studies, 2019)
The effect of poly acryl amide in the 15% HCl solution of carbon steel (class L-80) was studied using weight loss method , the efficiency of inhibitor increased by increasing inhibitor concentration and decreasing temperatures. Inhibition attributed to insoluble complex adsorbed on the coupon (L-80) carbon steel surface. The iron complex was identified by FTIR. And the mechanism of inhibition was explained as Langmuir adsorption isotherm. The thermodynamic parameters of adsorption operation was calculated and explained